Unveiling Cardiovascular Connections between Familial Hypercholesterolemia (FH) and Left Ventricular Hypertrophy (LVH) - Khan, Zoha; Suleman, Muhammad; Maqsood, Atif; Bashir, Bisma; Awais, Muhammad; Aslam, Muhammad Shahbaz (BioScientific Review, 2024)
Left ventricular hypertrophy (LVH), a complex cardiac condition characterized by the enlargement and thickening of the left ventricle, is primarily associated with hypertension and valvular heart disease. Recent studies have identified familial hypercholesterolemia (FH) as a secondary cause of LVH. It is characterized by high low-density lipoprotein cholesterol (LDL-C) in blood. FH is an inherited disorder which involves genetic variations associated with abnormal metabolism of LDL-C. This review article aims to provide a comprehensive overview of the relationship between FH and LVH. It summarizes the current understanding of the pathophysiological mechanisms underlying this association and discusses its implications for clinical practice. Elevated LDL-C levels in FH patients lead to accelerated atherosclerosis and an increased risk of premature cardiovascular events. Animal models and clinical observations provide insights into the mechanistic links between elevated LDL-C levels, oxidative stress, inflammation, and LVH development. Early diagnosis of FH would certainly play a critical role in preventing or delaying the development of LVH and subsequent cardiovascular complications. Preemptive measures emphasize the identification of at risk individuals, in-depth clinical evaluations, and implementation of effective treatments including lifestyle modifications, statins, and adjunctive therapies, such as PCSK9 inhibitors or lipoprotein apheresis. By increasing the awareness of FH as a secondary cause of LVH, healthcare professionals can improve early detection and implement appropriate management strategies to mitigate the cardiovascular burden associated with this inherited disorder.